Students' Sensory Perceptions of the Physical Setting of the Campus Environment (Case Study: Pradita Campus, Gading Serpong) (Lakar: Jurnal Arsitektur, 2026)
University students often experience academic and social pressures that negatively affect their mental health. A campus environment designed and equipped with natural elements that create restorative architecture can play a vital role in supporting users’ psychological recovery. Recent studies on restorative environments have largely focused on urban parks, healthcare settings, and therapeutic landscapes, while limited research applies the Perceived Sensory Dimensions (PSDs) framework to everyday academic environments, particularly within Indonesian private universities. By positioning the campus as a multisensory ecosystem that influences students’ cognitive and emotional resilience, this study advances the application of PSDs in higher education contexts and strengthens evidence-based approaches to restorative campus design. This study aims to analyze students’ perceptions of the campus environment as a restorative space based on the PSDs. A quantitative approach was used, with data collected through a Likert scale-based questionnaire (1–6). The survey received responses from 75 participants, all of whom were students. The results show that the majority of respondents agreed that the presence of natural elements, open spaces, tranquil atmospheres, and physical/psychological protection on campus helps reduce stress and enhance emotional comfort. However, the cultural and cohesive dimensions received more neutral or negative responses, indicating a need for re-evaluation of spatial designs that support cultural identity and spatial connectivity across campus areas. This study emphasizes the importance of integrating restorative design approaches in campus development to promote student well-being.
Keywords: campus environment; mental health; perceived sensory dimensions (PSDs); restorative environment; student perception